INFLUENCE FACTORS AND MANIFESTATIONS OF PRODUCTIVITY - DĂNECI-PĂTRĂU, Daniel; COCA, Elena Carmen (Annals of Spiru Haret University. Economic Series, 2014)
Notion almost unknown before 1950, labor productivity is now commonly used by economists, engineers, sociologists and politicians alike, influencing all the important issues of the time. Under these circumstances, if it is accepted that labor productivity is the driving variable that generates economic progress, it is justified that people need to increase their efforts to enhance, its value through various means. This article presents the findings of a theoretical research literature regarding landmarks in the evolution of labor productivity. Arguments justifying such an approach have been given by the fact that the labor issue presents an interest not only at the micro level, individual (the consequences it has on the individual work), but also at the macro level, societal (employment relations on the market labor, insurance systems and the offer educational services on the market today).